OPTIMALISASI KINERJA GURU DALAM PENGELOLAAN PEMBELAJARAN (Studi Deskriptif Kualitatif di SMPN Campur Sari, kabupaten Musi Rawas) - Nurdiyanto, Nurdiyanto (Manajer Pendididikan, 2025)
This study aims to describe the optimization of teacher performance in learning management at SMPN Campursari, Musi Rawas Regency. The optimization in question is the efforts made by principal, the efforts made by teachers and the obstacles faced. This research is a qualitative research using interview, observation, and documentatiton methodes for data collection. The stages of data management start from data collection , data reduction and drawing conclusions. The conclusion of this research is that the principal has made various efforts including routine coaching for teachers both individually and in groups, motivating teachers to continue learning, conducting academic supervision. penelitian ini efforts made by teachers include sel-learning, attending training, being avtive in MGMP and participating in the driving teacher program